Ramadan Mubarak - Khan,saniyasnain (china goodwordbooks, 2020)
This adorable book introduces little ones to Ramadan. The text is straight forward and illustrations are cute. It briefly touches on fasting, Qur'an, gratitude, generosity, kindness, prayer, Eid ul-Fitr and more